ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR CRUDE PALM OIL INDONESIA: PENDEKATAN VECTOR ERROR CORECTION MODEL - Angela Gracia Permata Hati; Birgitta Dian Saraswati; Yustinus Wahyudi (Fakultas Ekonomi Universitas Pekalongan, 2021)
Crude Palm Oil (CPO) is one of the non-oil exports that has the largest contribution to the total main exports of non-oil and gas commodities in Indonesia. This study aims to analyze the effect of exchange rates, CPO production, international CPO prices, and inflation rates on total CPO exports in Indonesia, and determine the shocks impact that occur on exchange rates, CPO production, international CPO prices, and inflation rates against CPO exports in Indonesia. This study used time series secondary data, namely monthly data for the 2010-2019 period. Using the vector error correction model (VECM) method, this study provides results that the exchange rate has a long-term effect on Indonesia's CPO export volume. Meanwhile, international CPO prices have a negative and significant effect on the volume of CPO exports only in the short term. However, the shock that occurs in international CPO prices will have a huge impact on the movement of Indonesia's CPO export volume. The implication is that the performance of CPO exports, which is shown by the increase in the volume of CPO exports, is strongly influenced by the price factor, both the relative price indicated by the Rupiah exchange rate indicator and international CPO price